Food application of germinated quinua and enhancement of its nutritional, biological and functional properties: A systematic review - Paucarchuco Soto, Joselin (2024)
The germination of quinua improves the content of polyphenols, flavonoids, amino acids, dietary fiber, vitamin E, antioxidants and other bioactive compounds, making this pseudocereal a nutritious and healthy source for the preparation of functional foods. The aim of this work was to assess the effect of the germination of quinua on the nutritional, biological and functional properties, in turn to be able to analyze the potential that this golden grain has in the food industry. For the systematic review, the databases (Scopus, Scielo and Science Direct) were used, following the PRISMA guideline and the PIO strategy (Population, Intervention, Outputs), which helped to formulate the search equations and to identify the most relevant articles of the last 5 years. The results of the bibliometric analysis showed that the germination of quinua improves the nutritional properties and the content of secondary metabolites, also represents a potential source for the development of food products with functional and nutraceutical properties. A recent study confirms that after 4 days of germination the total phenolic content of various types of quinua ranges between 39.29 and 782.15 mg/100 g, indicating a powerful ability to eliminate free radicals, turning this pseudocereal into a raw material with the ability to be applied in the formulation of various food products such as bread, cookies, pizzas, beverages, yogurt, cheeses, etc.